Three-dimensional continuous fiber network, preparation method of three-dimensional continuous fiber network, composite solid electrolyte, preparation method of composite solid electrolyte and solid lithium metal battery
By introducing a three-dimensional continuous fiber network into the PVDF-based solid electrolyte, including the heat-treated polyacrylonitrile fiber and metal organic frame, the poor compatibility and low ionic conductivity of the PVDF-based solid electrolyte between the high-voltage positive electrode and the lithium metal negative electrode are solved. The problem has significantly improved the cycle stability and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411674862.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The poor compatibility of existing PVDF-based solid electrolytes between high-voltage positive electrodes and lithium metal negative electrodes leads to poor cycle stability, low ion conductivity, and serious problems with heterogeneous ion flux, which affects battery performance and life.
A three-dimensional continuous fiber network, including heat-treated polyacrylonitrile fibers and metal organic frames, is used as a structure for composite solid electrolytes, and is prepared through solvothermal reactions to improve the continuity and stability of the ion transport channel.
It significantly improves the room temperature ion conductivity, lithium ion migration number and electrochemical window, inhibits the growth of lithium dendrites, achieves uniform lithium deposition, extends the battery cycle life, and improves the battery cycle and rate performance.
Smart Images

Figure CN119465644A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a three-dimensional continuous fiber network, a preparation method thereof, a composite solid electrolyte, a preparation method thereof, and a solid-state lithium metal battery. Background Art
[0002] Solid-state batteries are considered one of the most promising next-generation battery technologies due to their inherent high safety, especially the use of high-voltage positive electrodes and lithium metal negative electrodes can give full play to the high energy density advantages of solid-state batteries. Among the many solid-state electrolytes (SSEs), polymer solid electrolytes (SPEs) are considered to be feasible materials for large-scale industrial applications due to their excellent flexibility and interface contact properties. Currently, SPEs based on polyethylene, polyacrylonitrile, polypropylene carbonate, and polyvinylidene fluoride (PVDF) have been reported. Compared with other SPEs, polyvinylidene fluoride (PVDF)-based solid electrolytes have attracted much attention due to their excellent thermal stability and unique ion transport mechanism. The small amount of N,N-dimethylformamide (DMF) solvent remaining in the PVDF electrolyte can react with Li + The [Li(DMF) x ] + The composite structure can achieve ion transport through interaction with PVDF chains, but the residual DMF will significantly affect the compatibility between PVDF-based SSEs and high-voltage positive electrodes and lithium metal negative electrodes, thereby weakening the cycle stability of the battery. In addition, the low ionic conductivity of the PVDF matrix and its porous structure may also lead to problems with heterogeneous ion flux, which will not only cause uneven lithium deposition, but also accelerate dendrite growth. Especially at higher current densities, these side reactions and uneven lithium deposition behavior will be significantly aggravated, posing a serious threat to the performance and life of the battery.
[0003] The preparation of composite solid electrolytes (CSEs) using polymers as matrices is considered to be the most effective strategy to improve the electrochemical performance of solid-state batteries. The commonly used method is to prepare CSEs by introducing various active or inert fillers in the hope of obtaining CSEs with high ionic conductivity and excellent electrochemical stability. However, most CSEs are currently prepared by simply mixing the filler with the PVDF matrix. This single structural design makes it difficult to ensure the continuous and efficient transport of lithium ions in the electrolyte. Therefore, the ionic conductivity of PVDF-based CSE is often difficult to reach 10 -3 S cm -1 , which undoubtedly greatly limits its potential in practical applications.
[0004] Metal-organic frameworks (MOFs) are crystalline porous materials assembled from metal ions or inorganic clusters and organic ligands. Due to their good surface chemical properties, abundant pores and tunable structures, they have great potential in designing the structure of CSEs and are expected to provide new solutions for improving the ionic conductivity and optimizing the performance of PVDF-based CSEs.
[0005] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0006] In order to make up for the deficiencies of the prior art, the present invention provides a three-dimensional continuous fiber network, a preparation method thereof, a composite solid electrolyte, a preparation method thereof and a solid-state lithium metal battery.
[0007] The present invention adopts the following technical solution:
[0008] In a first aspect, a three-dimensional continuous fiber network is provided, which includes electrospun fibers and a metal organic framework, wherein the metal organic framework is uniformly and continuously distributed on the surface of the electrospun fibers, and the electrospun fibers are heat-treated polyacrylonitrile.
[0009] In a second aspect, a method for preparing the three-dimensional continuous fiber network according to the first aspect is provided, which comprises the following steps:
[0010] (1) dissolving polyacrylonitrile powder in N,N-dimethylformamide (DMF) solution until fully dissolved to prepare an electrospinning precursor solution;
[0011] (2) electrospinning the electrospinning precursor solution to prepare a polyacrylonitrile fiber precursor;
[0012] (3) calcining the polyacrylonitrile fiber precursor at 200-300° C. and then cooling naturally to obtain the polyacrylonitrile fiber;
[0013] (4) preparing a precursor solution of a metal organic framework;
[0014] (5) Immersing the polyacrylonitrile fiber in a precursor solution of the metal organic framework to perform a solvent thermal reaction to obtain the three-dimensional continuous fiber network.
[0015] In a third aspect, a composite solid electrolyte is provided, which includes polyvinylidene fluoride, a lithium salt and the three-dimensional continuous fiber network described in the first aspect, wherein in the composite solid electrolyte, the mass ratio of polyvinylidene fluoride to lithium salt is 1-1.5:1, and the mass fraction of the three-dimensional continuous fiber network is 20-30wt%.
[0016] In a fourth aspect, a method for preparing the composite solid electrolyte according to the third aspect is provided, comprising the following steps:
[0017] S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform solution;
[0018] S2, adding the three-dimensional continuous fiber network into the solution of step S1, removing bubbles by ultrasonication and vacuuming, and completely immersing the network;
[0019] S3, drying the completely immersed continuous fiber network and the solution, removing excess solvent, and obtaining a composite solid electrolyte membrane, that is, obtaining the composite solid electrolyte.
[0020] In a fifth aspect, a solid-state lithium metal battery is provided, which comprises the composite solid-state electrolyte described in the third aspect, a positive electrode and a lithium metal negative electrode.
[0021] The present invention has the following beneficial effects: the three-dimensional continuous fiber network of the present invention can construct a continuous ion transmission channel in a polymer matrix electrolyte, especially a PVDF matrix electrolyte, and improve the ion transport efficiency. The interaction between the three-dimensional continuous fiber network and the solvent molecules can weaken the coordination between lithium ions and solvent molecules, so that more lithium salt anions enter the solvation shell, prompting them to reduce and decompose on the surface of the lithium metal negative electrode and construct an electrode / electrolyte interface rich in inorganic components and stable, inhibiting the growth of lithium dendrites, uniform lithium deposition, and extending the cycle life of the battery. The h-PAN fiber after heat treatment in the three-dimensional continuous fiber network of the present invention still has a good fiber network structure, and the spinning fiber is uniform in thickness, the fiber diameter is about 200nm, and the MOF with good crystallinity grows on the surface of the h-PAN fiber, and the growth is continuous and uniform. The room temperature ionic conductivity, lithium ion migration number and electrochemical window of the composite solid electrolyte prepared by adding it to the polyvinylidene fluoride matrix are significantly improved. The Li||NCM811 solid-state battery prepared using it has excellent cycle and rate performance. The present invention has broad application prospects in the field of solid-state lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1a and 1b They are scanning electron micrographs of h-PAN and h-PAN@UIO-66-NH2 prepared in Example 1, respectively;
[0023] Figure 2a and 2b They are the transmission electron microscopy image and element distribution map of h-PAN@UIO-66-NH2 prepared in Example 1;
[0024] Figure 3 is the X-ray diffraction pattern of h-PAN@UIO-66-NH2 prepared in Example 1;
[0025] Figure 4a and 4b They are respectively an optical photograph and a cross-sectional scanning electron microscope image of the PUP solid electrolyte prepared in Example 1;
[0026] Figure 5a-5c They are respectively a local three-dimensional structure computed tomography (CT) image, a surface CT image and a cross-sectional CT image of the PVDF solid electrolyte prepared in Comparative Example 1;
[0027] Figure 5d-5f They are respectively the local three-dimensional structure CT image, surface CT image and cross-sectional CT image of the PUP solid electrolyte prepared in Example 1;
[0028] Figure 6a-6b They are the thermogravimetric curves of the electrolyte membrane prepared in Example 1 and the electrolyte membrane prepared in Comparative Example 1, respectively.
[0029] Figure 7 1 is the stress-strain curve of the electrolyte membrane prepared in Example 1 and Comparative Example 1;
[0030] Figure 8 It is a schematic diagram of the solvation structure in the PUP composite solid electrolyte of Example 1 and the PVDF solid electrolyte of Comparative Example 1.
[0031] Fig. 9 It is an analysis chart of the Raman test results of the PUP solid electrolyte prepared in Example 1 and the PVDF solid electrolyte prepared in Comparative Example 1.
[0032] Fig.10 These are infrared test images of the PUP solid electrolyte prepared in Example 1 and the PVDF solid electrolyte prepared in Comparative Example 1.
[0033] Fig.11a This is an atomic force microscope image of the PUP solid electrolyte prepared in Example 1;
[0034] Fig.11b for Fig.11a Nano-infrared microscope image of
[0035] Fig.12 It is a cycle performance test chart of the lithium metal battery assembled in Example 1 and Comparative Example 1 at 25°C and 5C rate after 1000 cycles. DETAILED DESCRIPTION
[0036] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following examples are all conventional commercial products or open source.
[0037] A specific embodiment of the present invention provides a three-dimensional continuous fiber network, which includes electrospun fibers and a metal organic framework, wherein the metal organic framework is uniformly and continuously distributed on the surface of the electrospun fibers, and the electrospun fibers are heat-treated polyacrylonitrile (h-PAN).
[0038] The present invention refers to the three-dimensional continuous fiber network as h-PAN@MOF network, and the electrochemical properties of the composite solid electrolyte using it as the framework and its performance in solid-state batteries are significantly improved.
[0039] In some embodiments, the metal organic framework is one of UIO-66 and UIO-66-NH2.
[0040] In some embodiments, the electrospun fiber is polyacrylonitrile after heat treatment at 200-300°C. After heat treatment at 200-300°C, the nitrile group of polyacrylonitrile forms a ring after cyclization and dehydration, which has high mechanical strength, and the lone pair of electrons of N on it can become Zr on the metal organic framework (MOF). 4+ The coordination sites of metal ions enable the continuous growth of MOF on the surface of electrospun fibers.
[0041] A specific embodiment of the present invention provides a method for preparing the three-dimensional continuous fiber network, which comprises the following steps:
[0042] (1) dissolving polyacrylonitrile powder in N,N-dimethylformamide (DMF) solution until fully dissolved to prepare an electrospinning precursor solution;
[0043] (2) electrospinning the electrospinning precursor solution to prepare a polyacrylonitrile fiber precursor;
[0044] (3) calcining the polyacrylonitrile fiber precursor at 200-300° C. and then cooling naturally to obtain the polyacrylonitrile fiber;
[0045] (4) preparing a precursor solution of a metal organic framework;
[0046] (5) Immersing the polyacrylonitrile fiber in a precursor solution of the metal organic framework to perform a solvent thermal reaction to obtain the three-dimensional continuous fiber network.
[0047] In some embodiments, the metal organic framework is UIO-66-NH2, and step (4) comprises the following steps:
[0048] (41) Dissolve zirconium chloride in DMF to obtain a colorless, transparent, clear solution A;
[0049] (42) 2-Aminoterephthalic acid was dissolved in DMF to obtain a yellow transparent solution B;
[0050] (43) Solution B was added dropwise to solution A, and glacial acetic acid was added to obtain a UIO-66-NH2 precursor solution, in which the mass ratio of zirconium oxide to 2-aminoterephthalic acid was 1-2:1.
[0051] A specific embodiment of the present invention provides a composite solid electrolyte, which includes polyvinylidene fluoride, lithium salt and the three-dimensional continuous fiber network, wherein in the composite solid electrolyte, the mass ratio of polyvinylidene fluoride to lithium salt is 1-1.5:1, and the mass fraction of the three-dimensional continuous fiber network is 20-30wt%.
[0052] In some embodiments, the lithium salt is at least one of lithium bis(fluorosulfonyl)imide (LIFSI), lithium bis(trifluorosulfonyl)imide, and lithium difluorooxalatoborate.
[0053] A specific embodiment of the present invention provides a method for preparing the composite solid electrolyte, which comprises the following steps:
[0054] S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform solution; preferably stirring for 2-4 hours, so that the polyvinylidene fluoride and lithium salt are completely dissolved in the organic solvent to obtain a uniform and transparent solution;
[0055] S2, adding the three-dimensional continuous fiber network into the solution of step S1, removing bubbles by ultrasonication and vacuuming, and completely immersing the network;
[0056] S3, drying the completely immersed continuous fiber network and the solution (drying time is 8 to 10 hours), removing excess solvent, and obtaining a composite solid electrolyte membrane, that is, obtaining the composite solid electrolyte.
[0057] In some embodiments, the organic solvent is one of N,N-dimethylformamide, acetamide and dimethyl sulfoxide.
[0058] In some embodiments, in step S2, the ultrasonic time is 0.5 to 1 h, the ultrasonic rate is 90 to 110 KHz, and the vacuum time is 1 to 2 h.
[0059] In some embodiments, in step S1, the amount of the organic solvent is 5-7 mL.
[0060] A specific embodiment of the present invention provides a solid-state lithium metal battery, which includes the composite solid-state electrolyte, a positive electrode and a lithium metal negative electrode.
[0061] The three-dimensional continuous fiber network of the present invention can construct a continuous ion transmission channel in a polymer matrix electrolyte, especially a PVDF matrix electrolyte, to improve the ion transport efficiency. The interaction between the three-dimensional continuous fiber network and the solvent molecules can weaken the coordination between lithium ions and solvent molecules, allowing more lithium salt anions to enter the interior of the solvation shell, prompting them to be reduced and decomposed on the surface of the lithium metal negative electrode and construct an inorganic component-rich and stable electrode / electrolyte interface, inhibiting the growth of lithium dendrites, uniform lithium deposition, and extending the cycle life of the battery.
[0062] The specific embodiments of the present invention are further described below.
[0063] Example 1
[0064] The method for preparing a three-dimensional continuous fiber network comprises the following steps:
[0065] (1) 1.2 g of polyacrylonitrile powder was dissolved in 15 mL of N,N-dimethylformamide (DMF) solution to prepare an electrospinning precursor solution, which was a yellow, transparent, and uniform slurry;
[0066] (2) electrospinning the electrospinning precursor solution to prepare a polyacrylonitrile fiber precursor; specifically, electrospinning is performed under the following parameters: spinning voltage -1 to 20 kV, driving rate 1.2 mL h -1 , spinning scanning speed is 15mms – 1 , spinning temperature 35℃, spinning humidity 40%, to prepare h-PAN fiber precursor membrane.
[0067] (3) calcining the polyacrylonitrile fiber precursor at 200-300° C. and then cooling naturally to obtain the polyacrylonitrile fiber; in this example, specifically, the PAN fiber precursor film is cut into a suitable size, stacked on a hard carbon paper, and heated at 3° C. min. -1 The heating rate was increased from room temperature to 240°C and kept at this temperature for 40 minutes. After that, the mixture was naturally cooled to room temperature to obtain the h-PAN fiber membrane.
[0068] (4) Preparing a precursor solution of UIO-66-NH2; in this example, specifically, dissolving 0.294 g of zirconium chloride in 50 mL of DMF to obtain a colorless, transparent, clear solution A; dissolving 0.228 g of 2-aminoterephthalic acid in 50 mL of DMF to obtain a yellow, transparent solution B; adding solution B dropwise to solution A, and adding 12 mL of glacial acetic acid, and ultrasonicating for 30 min to obtain a light yellow, transparent UIO-66-NH2 precursor solution.
[0069] (5) Immersing the polyacrylonitrile fiber in the precursor solution of the metal organic framework to perform a solvothermal reaction to obtain the three-dimensional continuous fiber network. Specifically, immersing the h-PAN fiber in the precursor solution to perform a solvothermal reaction in a polytetrafluoroethylene-lined steel autoclave to obtain a three-dimensional continuous fiber network h-PAN@UIO-66-NH2.
[0070] The preparation of the composite solid electrolyte includes the following steps:
[0071] S1. Under an inert atmosphere, weigh 267 mg of LiFSI, place it in a stirring bottle, add 6 mL of DMF, and stir 400 mg of PVDF on a small stirrer at room temperature for more than 4 hours until LiFSI and PVDF are completely dissolved to obtain a uniform transparent solution;
[0072] S2. Add the three-dimensional continuous fiber network prepared above into the solution of step S1, remove bubbles by ultrasonication and vacuumization, and completely immerse; wherein, the ultrasonication time is 0.5 to 1 hour, the ultrasonication rate is 90 to 110 KHz, and the vacuumization time is 1 to 2 hours.
[0073] S3. Pour the completely immersed three-dimensional continuous fiber network and the solution into a container (such as a glass culture dish) and place it in an oven (such as a forced air oven, 55°C) to dry for 8 hours. Remove excess DMF to obtain a composite solid electrolyte membrane (wherein the three-dimensional continuous fiber network accounts for 30wt% of the mass of the composite solid electrolyte membrane), referred to as PUP solid electrolyte in this article, punch it into a suitable size, and store it in an inert atmosphere for dry storage before use.
[0074] The NCM811 positive electrode, PUP solid electrolyte and lithium metal are assembled into a full battery according to the same battery assembly process as in Comparative Example 1.
[0075] Comparative Example 1
[0076] This comparative example 1 provides a PVDF solid electrolyte and a method for assembling a full battery, which at least includes the following steps:
[0077] S1. First, weigh 267 mg of LiFSI under an inert atmosphere, place it in a stirring bottle, add 6 mL of DMF, and stir 400 mg of PVDF on a small stirrer at room temperature for more than 4 hours until LiFSI and PVDF are completely dissolved to obtain a uniform transparent solution.
[0078] S2. Pour the solution obtained in step S1 into a glass culture dish, place it in a 55°C forced air oven and dry it for 8 hours to remove excess solvent DMF to obtain a PVDF solid electrolyte membrane, punch it into a suitable size, and store it in an inert atmosphere for drying and use.
[0079] Then, the NCM811 positive electrode, PVDF polymer electrolyte and lithium metal are combined into a full battery according to the battery assembly process.
[0080] Taking button battery (CR2032) as an example, the assembly process is as follows:
[0081] 1. Material preparation: Cut the NCM811 positive electrode into φ12mm discs; the lithium sheet size is φ15.6mm; cut the PVDF solid electrolyte membrane into φ19mm discs
[0082] 2. Assembly sequence: from bottom to top, negative electrode shell - spring - gasket - lithium metal - solid electrolyte (PVDF solid electrolyte membrane) - NCM811 positive electrode - gasket - positive electrode shell. The above steps are carried out in a glove box filled with argon.
[0083] 3. Use a tablet press to press the assembled battery at a pressure of 50 kg cm -2 .
[0084] A series of tests were performed on Example 1 and the comparative example, and the results were as follows:
[0085] The microstructures of h-PAN and h-PAN@UIO-66-NH2 prepared in Example 1 were observed by scanning electron microscopy (SEM). Figure 1a It can be seen that the h-PAN fibers after heat treatment still have a good fiber network structure, and the spun fibers are uniform in thickness, with a fiber diameter of about 200 nm. Figure 1b It can be seen that MOF with good crystallinity grows on the surface of h-PAN fibers, and the growth is continuous and uniform.
[0086] Figure 2a and 2b They are transmission electron microscope image and element distribution diagram of h-PAN@UIO-66-NH2 prepared in Example 1. The element distribution in h-PAN@UIO-66-NH2 was tested by energy dispersive X-ray spectrometer (EDS) equipped with TEM. Figure 2a and 2bAs shown, since both h-PAN and MOF contain a large amount of carbon, the distribution of carbon can be seen in the spectrum; the oxygen element in MOF is richer than that in h-PAN, and it can be seen that the oxygen element is mainly distributed on both sides of the sample spectrum, and less in the middle; since zirconium only exists in the MOF of the sample, it can be clearly seen that zirconium is distributed in the area corresponding to MOF.
[0087] The crystalline phase of h-PAN@UIO-66-NH2 prepared in Example 1 was confirmed by X-ray diffraction (XRD). Figure 3 As shown in the figure, the XRD pattern of h-PAN fiber shows broad diffraction peaks near 16° and 22°, corresponding to its amorphous state. After the growth of MOF, two strong characteristic diffraction peaks belonging to the (111) and (002) lattice planes of the crystalline MOF appeared. The XRD of the synthesized MOF matches well with the theoretically simulated MOF, and the synthesized MOF is pure phase.
[0088] Figure 4a and 4b The optical photo and cross-sectional scanning electron microscope image of the PUP solid electrolyte prepared in Example 1 show that after adding the h-PAN@MOF network to the polymer PVDF electrolyte, the membrane surface becomes dense and the pores are significantly reduced. Figure 4b As shown, the thickness of the PUP solid electrolyte prepared in Example 1 is about 90 μm, and the cross section is dense and uniform.
[0089] Computed tomography (CT) was performed to observe and reconstruct the three-dimensional internal bulk structure of PVDF solid electrolyte and PUP solid electrolyte. Figure 5d-5f As shown in Figure 2, the bulk structure of the PUP solid electrolyte is dense and uniform, which may be due to the h-PAN@MOF network providing more nucleation sites during the crystallization of PVDF. Figure 5a-5c The PVDF solid electrolyte shown has a loose and porous structure.
[0090] The residual amount of solvent in PVDF solid electrolyte and PUP solid electrolyte was tested. Figure 6a-6b As shown in the figure, the mass fractions of residual DMF in the PUP solid electrolyte and PVDF solid electrolyte in the electrolyte membrane are 18.3wt% and 19.8wt%, respectively, and the residual solvent contents are almost the same.
[0091] Conduct tensile strength tests such as Figure 7 As shown in the stress-strain curve, the electrolyte membrane prepared by adding h-PAN@MOF (Example 1) can greatly improve its mechanical strength, and the tensile strength of the PUP solid electrolyte membrane can reach 20.84 MPa.
[0092] The residual solvent in the PUP solid electrolyte of Example 1 will coordinate with the lithium salt to form a solvation structure, such as Figure 8 Schematic diagrams of the solvation structures of Example 1 and Comparative Example 1 are shown (in the figure, AGG represents anion aggregates, AGG-1 represents a lithium ion surrounded by two lithium salt anions, AGG-2 represents a lithium ion surrounded by multiple lithium salt anions, and CIP represents a contact ion pair). Fig. 9 This is the Raman test result analysis diagram of PUP solid electrolyte and PVDF solid electrolyte. Fig. 9 The test results show that the anion aggregates (AGGs) component in the PUP solid electrolyte increased, indicating that the introduction of the h-PAN@UIO-66-NH2 fiber network regulated the solvation structure in the composite solid electrolyte.
[0093] In order to study the mechanism of action of the composite solid electrolyte in the present invention, infrared tests were performed on the PUP solid electrolyte. Fig.10 As shown, the free peaks of C=O and -CH3 of DMF in the PUP solid electrolyte were blue-shifted, indicating that there was a strong interaction between MOF and DMF, which helped to weaken the coordination of lithium ions with DMF.
[0094] Atomic force microscopy tests were performed on the PUP solid electrolyte. Fig.11a and 11b As shown, it can be seen that the absorption peak intensity at the infrared spectrum along the h-PAN@UIO-66-NH2 fiber network is much stronger than that in the PVDF matrix, indicating that there is a higher adsorption energy between MOF and DMF molecules, so that more lithium salt anions participate in the interior of the solvation structure and form more AGGs components.
[0095] The lithium metal batteries assembled in Example 1 and Comparative Example 1 were subjected to cycle performance tests. Fig.12 , Fig.12 The figure is a cycle performance test chart of the lithium metal battery assembled in Example 1 and Comparative Example 1 at 25°C and 5C rate, and cycled for 1000 cycles. Under the same conditions, the lithium metal battery assembled with the composite solid electrolyte prepared in Example 1 can stably cycle for 1000 cycles with a capacity retention rate of 72.8%, while the lithium metal battery assembled with the PVDF solid electrolyte without adding the three-dimensional continuous fiber network in Comparative Example 1 fails at about 180 cycles, and the capacity retention rate decreases rapidly.
[0096] Therefore, the MOF crystals continuously grown on the fibers proposed in the present invention provide an efficient continuous linear channel for lithium ion transport, thereby significantly improving the ionic conductivity to 1.03×10 -3 Scm -1Based on the high mechanical strength of h-PAN@MOF, the tensile strength of the prepared PUP solid electrolyte membrane reached 20.84MPa. In addition, the interaction between MOF and the solvated molecules also changed the distribution of the solvated structure in the electrolyte, making more FSI - The ability to enter the solvation shell is more conducive to the formation of a stable solid electrolyte interface (SEI) rich in inorganic components, which greatly enhances the stability of the electrolyte to lithium metal, thereby ensuring that the battery can operate stably for a long time. The prepared PUP solid electrolyte exhibits significant electrochemical performance advantages due to its extremely high ionic conductivity and excellent interface stability. At room temperature, it can show stable cycling performance regardless of low or high current density, especially at a current density of 1 mA cm -2 The dough capacity is 1 mAh cm -2 Under the condition of 1C, the battery can stably cycle for about 160 hours. The full battery matching NCM811 positive electrode and lithium metal negative electrode has significantly improved the discharge capacity and cycle stability at high rates, especially at a rate of up to 5C, which can show 118.2mAh g -1 The invention provides a feasible strategy for improving the ionic conductivity and interface stability of the solid electrolyte through structural design.
[0097] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A three-dimensional continuous fiber network, characterized in that: The invention comprises an electrostatic spinning fiber and a metal organic framework, wherein the metal organic framework is evenly and continuously distributed on the surface of the electrostatic spinning fiber, and the electrostatic spinning fiber is heat-treated polyacrylonitrile.
2. The three-dimensional continuous fiber network according to claim 1, characterized in that: The metal organic framework is one of UIO-66 and UIO-66-NH2; the electrospinning fiber is polyacrylonitrile heat-treated at 200-300°C.
3. A method for preparing the three-dimensional continuous fiber network according to claim 1, characterized in that: The steps include: (1) dissolving polyacrylonitrile powder in N,N-dimethylformamide (DMF) solution until fully dissolved to prepare an electrospinning precursor solution; (2) electrospinning the electrospinning precursor solution to prepare a polyacrylonitrile fiber precursor; (3) calcining the polyacrylonitrile fiber precursor at 200-300° C. and then cooling naturally to obtain the polyacrylonitrile fiber; (4) preparing a precursor solution of a metal organic framework; (5) Immersing the polyacrylonitrile fiber in a precursor solution of the metal organic framework to perform a solvent thermal reaction to obtain the three-dimensional continuous fiber network.
4. The preparation method according to claim 3, characterized in that: The metal organic framework is UIO-66-NH2, and step (4) comprises the following steps: (41) Dissolve zirconium chloride in DMF to obtain a colorless, transparent, clear solution A; (42) 2-Aminoterephthalic acid was dissolved in DMF to obtain a yellow transparent solution B; (43) Solution B was added dropwise to solution A, and glacial acetic acid was added to obtain a UIO-66-NH2 precursor solution, in which the mass ratio of zirconium oxide to 2-aminoterephthalic acid was 1-2:
1.
5. A composite solid electrolyte, characterized in that: It comprises polyvinylidene fluoride, lithium salt and the three-dimensional continuous fiber network according to any one of claims 1-2, wherein in the composite solid electrolyte, the mass ratio of polyvinylidene fluoride to lithium salt is 1-1.5:1, and the mass fraction of the three-dimensional continuous fiber network is 20-30wt%.
6. The composite solid electrolyte according to claim 5, characterized in that The lithium salt is at least one of lithium bis(fluorosulfonyl)imide (LIFSI), lithium bis(trifluorosulfonyl)imide, and lithium difluorooxalatoborate.
7. A method for preparing the composite solid electrolyte according to any one of claims 5 to 6, characterized in that: The steps include: S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform solution; S2, adding the three-dimensional continuous fiber network into the solution of step S1, removing bubbles by ultrasonication and vacuuming, and completely immersing the network; S3, drying the completely immersed continuous fiber network and the solution, removing excess solvent, and obtaining a composite solid electrolyte membrane, that is, obtaining the composite solid electrolyte.
8. The preparation method according to claim 7, characterized in that: The organic solvent in step S1 is one of N,N-dimethylformamide, acetamide and dimethyl sulfoxide.
9. The preparation method according to claim 8, characterized in that: In step S2, the ultrasonic time is 0.5 to 1 h, and the ultrasonic rate is 90 to 110 KHz; the vacuum time is 1 to 2 h; in step S1, the amount of the organic solvent is 5 to 7 mL.
10. A solid-state lithium metal battery, characterized in that: It comprises the composite solid electrolyte according to any one of claims 5 to 6, a positive electrode and a lithium metal negative electrode.